PLA2R-IgG4 antibody as a predictive biomarker of treatment effectiveness and prognostic evaluation in patients with idiopathic membranous nephropathy: a retrospective study - Huang,Yiqing; Zhou,Junyi; Zhou,Kezhi; Huang,Biao; Xue,Jing; Zhang,Xiran; Liu,Bin; Zhang,Zhijian; Zhou,Leting; Cai,Ting; Zhang,Yi; Hu,Zhigang; et al. (PeerJ, 2022)
Background The Kidney Disease Improving Global Outcomes (KDIGO) 2021 guidelines recommend Rituximab (RTX) as the first-line therapy and phospholipase A2 receptor (PLA2R) antibody as a biomarker for remission and prognosis in patients with idiopathic membranous nephropathy (IMN). Methods This study was a retrospective analysis of 70 patients with IMN treated with either rituximab (RTX) or cyclophosphamide (CTX) and steroid. Quantitative detection of PLA2R-IgG and PLA2R-IgG4 antibodies at sixth month after treatment, determined using time-resolved fluoroimmunoassay (TRFIA), were used for treatment effectiveness analysis and prognostic evaluation in patients with IMN. Results After 12 months of therapy, the remission rate of proteinuria, including complete remission (CR) and partial remission (PR) in the RTX group and the CTX group, were 74% versus 67.5% (P = 0.114), respectively. Both PLA2R-IgG and PLA2R-IgG4 levels were decreased in patients with remission of proteinuria after 6 months of therapy. Receiver operating characteristic curve (ROC) curve analysis exhibited that the AUC of PLA2R-IgG4 and the PLA2R-IgG as laboratory criteria for proteinuria remission were 0.970 versus 0.886 (P = 0.0516), respectively, after 6 months of treatment. The cut-off value of PLA2R-IgG4 was 7.67 RU/mL and the sensitivity and specificity of remission rate at 6th month were 90.9% and 100%, respectively. Furthermore, the AUC of the PLA2R-IgG4 and PLA2R-IgG to predict the outcome after 12 months of treatment were 0.922 versus 0.897 (P = 0.3270), respectively. With the cut-off value of PLA2R-IgG4 being 22.985 RU/mL, the sensitivity and specificity of remission rate at 12th month were 100% and 87.1%, respectively. Logistic regression analysis revealed that the PLA2R-IgG4 level (P = 0.023), the rate of decrease of PLA2R-IgG4 level (P = 0.034), and eGFR level (P = 0.012) were significantly associated with remission. Conclusions We found that the patients in the RTX group and CTX group achieved effective remission of proteinuria after 12 months of treatment. PLA2R-IgG4 may be a more effective biomarker for treatment effectiveness analysis and prognostic assessment, compared with anti-PLA2R-IgG for PLA2R associated IMN.
Keywords: M-type phospholipase A2 receptor; IgG4; Time-resolved fluoroimmunoassay; Rituximab; Idiopathic membranous nephropathy